The financial management practices of state mosques in Peninsular Malaysia - Siraj, Siti Alawiah; Mohamed_Ibrahim, Shahul Hameed; Sulaiman, Maliah (Trisakti University, 2007)
Scandals involving fraud and embezzlement of significant amounts of the financial resources of Western Church Institutions are increasingly becoming more common. Such scandals have raised concerns as to the ability of internal control systems within the organisations to restrict such occurrences. Although no such scandals have been reported for Islamic organisations, to date (particularly mosques), tehre is concern as to whether these organizations experience the same deficiencies as the Wstern church institutions. As such, the study examines the existing financial management practices of state mosques in Peninsular Malaysia, particularly in the areas of budgeting, receipts of income, disbursement of funds and reporting. A questionnaire survey and face-to-face interviews were employed in collecting the data. The results of the study indicate the state mosques in Peninsular Malaysia have a strong internal control system pertaining to receipts of income and disbursement of funds. However, state mosques are still lacking in budgetary and reproting controls. the study also reveals that basic internal control activities such as segregation of duties, recording of financial transactions and authorization of particular activities are satisfactorily practiced within the state mosques. Although this is an explratory study, the results may provide a benchmark for further studies in the financial management practices of Islamic organizations in Malaysia.